Lupus enhancer risk variant causes dysregulation of IRF8 through cooperative lncRNA and DNA methylation machinery - Zhou, Tian; Zhu, Xinyi; Ye, Zhizhong; Wang, Yong-Fei; Yao, Chao; Xu, Ning; Zhou, Mi; Ma, Jianyang; Qin, Yuting; Shen, Yiwei; Tang, Yuanjia; Yin, Zhihua; et al. (Nature communications, 2022)
Despite strong evidence that human genetic variants affect the expression of many key transcription factors involved in autoimmune diseases, establishing biological links between non-coding risk variants and the gene targets they regulate remains a considerable challenge. Here, we combine genetic, epigenomic, and CRISPR activation approaches to screen for functional variants that regulate IRF8 expression. We demonstrate that the locus containing rs2280381 is a cell-type-specific enhancer for IRF8 that spatially interacts with the IRF8 promoter. Further, rs2280381 mediates IRF8 expression through enhancer RNA AC092723.1, which recruits TET1 to the IRF8 promoter regulating IRF8 expression by affecting methylation levels. The alleles of rs2280381 modulate PU.1 binding and chromatin state to regulate AC092723.1 and IRF8 expression differentially. Our work illustrates an integrative strategy to define functional genetic variants that regulate the expression of critical genes in autoimmune diseases and decipher the mechanisms underlying the dysregulation of IRF8 expression mediated by lupus risk variants. The functional effects of genetic loci associated with autoimmune disease are not well understood. By dissecting an autoimmune disease genetic locus, the authors define an immune cell-type-specific enhancer and the molecular mechanisms underlying the dysregulation of IRF8 expression by lupus risk variants.